(untitled) - Sugimoto, Masayoshi (Cambridge, Mass, 1978)
Science and Culture in Traditional Japan (A.D. 600-1854) begins with the first Chinese Cultural Wave, in which Chinese science was introduced into Japan but not completely assimilated. The book then goes on to show how social and political conditions led to patterns of deliberate withdrawal from outside cultural influences, introducing in turn some five centuries of indigenous development. It tells of the pressures for a modern society with the second Chinese Cultural Wave and the first Western Cultural Wave in the sixteenth century; how the Western school of thought was largely ignored in favor of the Eastern tradition; and details the social and intellectual factors that would eventually challenge Japanese isolationism and force a confrontation with the modern Western scientific traditions in the nineteenth century. The book concentrates on the three traditional fields of Japanese science—astrology and calendrical astronomy, mathematics, and medicine—and includes extensive tables and historical charts covering scientific activity over ten centuries.
Keywords: Science,Khoa học; History,Lịch sử; Japan,Nhật Bản